Nursing approach to myocardial infarction - P. R., Nandeesh Kumar (International Journal of Research in Medical Sciences, 2025)
Myocardial infarction (MI) is still a primary cause of death and disability globally, needing early, professional, and comprehensive healthcare measures. Nurses have an important role in all phases of MI treatment, from emergency response and acute clinical management to rehabilitation, education, and long-term follow-up. This study focuses on nurses' numerous tasks, which include fast evaluation, ECG monitoring, medication administration, emotional support, patient and family education, and multidisciplinary care coordination. Nurses in critical care settings help to prevent problems while also contributing considerably to quality improvement and evidence-based procedures. Nurse-led cardiac rehabilitation and follow-up clinics have shown improved outcomes and decreased recurrence. Furthermore, nurses promote patient autonomy, make ethical decisions, and participate in cardiovascular research. Addressing issues including intense workload, fatigue, and patient nonadherence is critical to improving nursing care. Following a MI, a thorough, patient-centered, and evidence-informed nursing strategy is required to improve survival, improve rehabilitation, and promote lifestyle modification.